An overview of Chinese agricultural and rural engagement in Tanzania - Bräutigam, Deborah; Tang, Xiaoyang (International Food Policy Research Institute, 2012)
The recent expansion of Chinese economic engagement in Africa is often poorly documented and not well understood. This paper is the second in an IFPRI-sponsored effort to better understand Chinese engagement in Africa’s agricultural sector. A clearer picture of Chinese activities in agriculture is important as a foundation for Africans and their development partners to more fruitfully engage with an increasingly important actor. Chinese engagement in agriculture and rural development in Tanzania is long-standing. Changes in this engagement reflect the changes in China’s engagement in Africa more generally. This overview paper explores China’s engagement in historical perspective, focusing on foreign aid, other official engagement, and investment by Chinese firms between 1964 and 2011.